PENGARUH KONSELING QUR’ANI UNTUK MENURUNKAN TINGKAT DEPRESI PADA MAHASISWA - komalasari, shanty (Faculty of Ushuluddin and Humanities, 2018)
This research aims to know the difference between the experimental group given intervention with Quranic counseling and a control group without intervention. This is quasi-experimental research that used untreated control group design with pretest and posttest. The subjects of this research were 20 students of UIN Antasari Banjarmasin that have passed the screening test. They were divided into an experimental group and control group, each of which consisted of 10 people. After the data were analyzed using non-parametric Mann-Whitney test, it was found out that = - 1553; sig = 0.121 (p>0,05), which means there was no significant difference between the level of depression on students in the experimental group after the intervention and the level of depression on students in control group. Afterward, according to the analysis result on Wilcoxon score in the post-test and interview by the experimental group, it was found out that Z score = - 0,609a and p score = 0,542; therefore, p > 0,05. It means Quranic counseling is relatively effective to decrease the level of depression on the students. Despite there was no significant difference between the experimental group and control group, the depression level on the experimental group, however, did not increase even though the Quranic counseling had been given over two weeks before.